The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1044/1058-0360.0901.10
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Service Delivery Models: Effects on Curricular Vocabulary Skills in the School Setting

Abstract: The present study evaluated the effectiveness of three service delivery models in the elementary school setting. Differences were investigated between (a) a collaborative approach, (b) a classroom-based intervention model with the speech-language pathologist (SLP) and classroom teachers working independently, and (c) a traditional pull-out model for children in kindergarten through third grade who qualified for speech or language services. The same curricular vocabulary targets and materials were used in all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 14 publications
3
82
0
1
Order By: Relevance
“…Each of these studies investigated the role of service delivery models on children's outcomes (i.e., vocabulary, functional communication, and language/literacy); no studies investigating the role of frequency/intensity met inclusion criteria for this review. Results across these five studies were mixed: two studies found service delivery models to have differential impacts on children's outcomes (see Bland & Prelock, 1995;Throneburg, Calvery, Sturm, Paramboukas, & Paul, 2000) while the other three found no significant differences (see Boyle, McCartney, Forbes, & O'Hare, 2007;Howlin, 1981;Kohl, Wilcox, & Karlan, 1978). There was preliminary evidence to suggest that classroom-based services may promote generalization of skills to novel settings; however, the most striking finding from this review was the glaring lack of high-quality, evidence-based research available to SLPs in choosing effective service-delivery models for school-age children with speech-language impairments.…”
Section: Resultsmentioning
confidence: 95%
“…Each of these studies investigated the role of service delivery models on children's outcomes (i.e., vocabulary, functional communication, and language/literacy); no studies investigating the role of frequency/intensity met inclusion criteria for this review. Results across these five studies were mixed: two studies found service delivery models to have differential impacts on children's outcomes (see Bland & Prelock, 1995;Throneburg, Calvery, Sturm, Paramboukas, & Paul, 2000) while the other three found no significant differences (see Boyle, McCartney, Forbes, & O'Hare, 2007;Howlin, 1981;Kohl, Wilcox, & Karlan, 1978). There was preliminary evidence to suggest that classroom-based services may promote generalization of skills to novel settings; however, the most striking finding from this review was the glaring lack of high-quality, evidence-based research available to SLPs in choosing effective service-delivery models for school-age children with speech-language impairments.…”
Section: Resultsmentioning
confidence: 95%
“…Mediated-learning and bridging strategies were shown to have positive effects on a verbal analogy task (Masterson & Perrey, 1999). Improvements on vocabulary performance were found with a collaborative, classroom-based service-delivery model when compared with the more traditional pull-out therapy approach (Throneburg, Calvert, Sturm, Paramboukas, & Paul, 2000). Interactive conversational reading strategies were also shown to have positive effects on receptive and expressive vocabulary (Crowe, 2003).…”
Section: Semantics and Vocabularymentioning
confidence: 96%
“…Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/terms-and-conditions INTRODUCTION One of the questions in speech language pathology (SLP) practice is how best to support children who attend formal child care. With resource constraints, there is a move from an individual or small group model of direct SLP practice to team teaching, consultation, and professional development of early childhood professionals (ECPs; McIntosh, Crosbie, Holm, Dodd, & Thomas, 2007;Throneburg, Calvert, Sturm, Paramboukas, & Paul, 2000). These latter indirect models of SLP practice reflect system-wide/population approaches and are due to factors such as SLP workforce shortages and the need for ECP training in the areas of language and literacy.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%